In-depth immunorecognition and neutralization analyses of Micrurus mipartitus and M. dumerilii venoms and toxins by a commercial antivenom (2024)
ABSTRACT: In Colombia, the Micrurus genus comprises 30 species, including M. mipartitus and M. dumerilii, which are of major clinical relevance due to their wide geographical distribution and the number of snakebites inflicted by them. These neurotoxic envenomations are characterized by neuromuscular paralysis attributed to venom components such as three-finger toxins (3FTx) and phospholipases (PLA2). Additionally, there is limited information available on the neutralizing coverage of commercially available antivenoms, underscoring the need to perform studies to assess the cross-neutralizing ability of these life-saving products. Therefore, we present an in-depth immunorecognition analysis by the anticoral-INS antivenom from Colombia on the M. mipartitus and M. dumerilii venoms. The antivenom crossrecognized the whole venoms and their components with different intensities. For instance, the antivenom showed better recognition on PLA2s than on 3FTxs in both venoms. Moreover, at doses tested, the antivenom totally neutralized the lethal effect of M. dumerilii venom; however, it did not neutralize this effect induced by M. mipartitus venom and its main toxic components from the southwestern region of the department of Antioquia. Furthermore, the anticoral-INS antivenom displayed better crossimmunorecognition of PLA2-predominant Micrurus venoms than of 3FTx-predominant Micrurus venoms. This highlights the need to include venoms from both types of venom patterns in the immunization mixture to produce antivenoms against coral snakes. Finally, our results suggest the need for further research to optimize the composition of immunizing mixtures for antivenom production and improve their efficacy against coral snake envenomation in Colombia and the Americas.